The impact of career calling on higher vocational nursing students’ learning engagement: The mediating roles of career adaptability and career commitment - Chen, Jingyuan; Zhang, Xiaoxia (Frontiers in Psychology, 2023)
As learning engagement is recognized as an important predictor of learners' academic success and an indicator of the quality of education, enhancing learners' engagement in learning has become a focus of educational researchers. Previous studies have explored strategies to enhance learning engagement in terms of pedagogical approaches, pedagogical strategies, pedagogical content and teacher-student interaction, but there is still a gap in the relationship between individual learners' internal mechanisms and learning engagement. To address this gap, this study explores the direct effects of career calling on higher vocational nursing students' learning engagement as well as the mediating roles of career adaptability and career commitment by constructing a parallel mediation model. Data were collected from 388 nursing students at two higher vocational colleges in China. Correlation and regression analyses were used to test the proposed hypotheses. The results showed that career calling has a significant positive impact on nursing students’ engagement in learning, with career adaptability and career commitment serving as important mediating effects. These findings also provide a foundation for promoting nursing students’ level of learning engagement and the design of instructional activities for the healthcare profession.